تصميم الكتاب المساند لكتاب النحو الواضح (الجزء الأول) لترقية مهارة الكلام لدى طلاب وطالبات الفصل السابع بمعهد محمدية الاسلامي عبد الرزاق فخر الدين يوكياكرتا - Asyiraf, Dara; Hafidah, Hafidah (El-Hayah, 2022)
The aims of this research are to develop educational teaching materials using supporting books to improve the speaking skills of seventh graders at PPM MBS Ar-Fachrudin Yogyakarta. and Knowing the characteristics of teaching materials after being implemented in the educational process. and Knowing the effectiveness of the Teaching Materials. Researchers use empirical field studies to develop their research, using development research methods in the ADDIE model (analysis, design, development, implementation and evaluation). Data collection methods in this study were observation, interviews, questionnaires and tests. The sample of the research community was the seventh semester students, twenty samples were taken as the control group and twenty samples for the experimental group. The results showed that educational materials were effective for improving speaking skills in the seventh semester, depending on the results obtained for the post-test, the researcher found that the t-account degree (t_o) in this study (3.7 ) was greater than the t-table degree. (t_t) at the level of (0.01 = 2.861) and (0.05 = 2.539).